2015
DOI: 10.1162/jocn_a_00682
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral and Neural Effects of Language on Motion Perception

Abstract: Abstract■ Perception does not function as an isolated module but is tightly linked with other cognitive functions. Several studies have demonstrated an influence of language on motion perception, but it remains debated at which level of processing this modulation takes place. Some studies argue for an interaction in perceptual areas, but it is also possible that the interaction is mediated by "language areas" that integrate linguistic and visual information. Here, we investigated whether language-perception in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 40 publications
4
37
3
Order By: Relevance
“…6). Combined, our results contradict claims that knowledge affects perception only at a very late stage 49,20,50 and provide general support for predictive processing accounts of perception, positing that knowledge may feedback to modulate lower levels of perceptual processing 3,25,51 .…”
Section: Discussioncontrasting
confidence: 86%
“…6). Combined, our results contradict claims that knowledge affects perception only at a very late stage 49,20,50 and provide general support for predictive processing accounts of perception, positing that knowledge may feedback to modulate lower levels of perceptual processing 3,25,51 .…”
Section: Discussioncontrasting
confidence: 86%
“…For instance, there is evidence that prior expectations decrease the distance to threshold for the more likely choice (Edwards, 1965), for instance, by priming relevant feature-selective sensory neurons (Kok et al, 2014; Shulman et al, 1999). However, conflicting reports have suggested that top-down signals serve to increase the rate of evidence accumulation for a particular choice (Diederich & Busemeyer, 2006), for instance, by improving the quality of signal read-out from competing pools of sensory neurons (Cravo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a growing body of evidence to suggest that the brain proactively facilitates perception by constructing feature-level models or templates of expected stimuli (Clark, 2013; Summerfield & Egner, 2009). Neural correlates of predictive stimulus templates have been observed in visual (Jiang, Summerfield, & Egner, 2013; Kok, Failing, & de Lange, 2014; Summerfield, Egner, Greene, et al, 2006; White, Mumford, & Poldrack, 2012), auditory (Chennu et al, 2013), somatosensory (Carlsson, Petrovic, Skare, Petersson, & Ingvar, 2000), and olfactory (Zelano, Mohanty, & Gottfried, 2011) cortex, highlighting feature prediction as a fundamental property of perception. It follows that feature-level predictions are compared with incoming sensory signals to determine a match between the expected and observed inputs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Does such a verbal cue affect the forward displacement of a moving object like nonverbal auditory cues (e.g., tone)? The language processing influences visual motion perception such as detection of low-level motion (Meteyard, Bahrami, & Vigliocco, 2007) and motion discrimination (Francken, Kok, Hagoort, & de Lange, 2015; Francken, Meijs, Hagoort, van Gaal, & de Lange, 2015; Pavan, Skujevskis, & Baggio, 2013). In the experiments in these studies, verbs representing directional movement (e.g., sink) were presented before a visual motion stimulus appeared, and the motion verbs congruent or incongruent with visual motion direction affected the error rate and reaction time of motion discrimination (e.g., Meteyard et al., 2007).…”
mentioning
confidence: 99%